İslâm Eğitim Tarihinde Müesseseleşme - Gözütok, Şakir (Dinî araştırmalar, 2006)
This article includes the establishment period of general Muslim educational institutions from the beginning of hijri century (7th A.D.). As it is known, mosques were the main educational institutions in Islamic world till the latter part of 5th century (hijri), and after this time they are gradually replaced by the madrasahs. In the less than a hundred and fifty years after the establishment of the first madrasah in Khurasan, they spread all over the Islamic world and constituted the most widespread educational system of this period. In fact, they were not the only institutions in Islamic educational system. Meanwhile other remarkable Islamic educational institutions, e.g. kuttabs, which were also known in the pre-Islamic Arabia, Dar al-Qurans, Dar al-Hadiths, Khanaqahs, Ribats and Zawiyays were also established or developed. And all of them provided accommodation facilities and salaries for professors, sheiks and students though some special financial arrangements. With these entire institutions Islamic social, cultural and educational milieu is created